Optimal portfolio strategy: A stock index-based analysis - Darma Saputra; Irwan Trinugroho; Faizul Mubarok (Sebelas Maret Business Review, 2025)
The classification of stock indices published by Indonesia Stock Exchange (2021) has resulted in variations of stock indices, whereby a stock index may contain stocks that are the same, similar, or different from other stock indices. Based on the portfolio theory in Hartono (2014) and the Markowitz model in Lutfi and Hendrian (2020), variations or differences in portfolio performance can be influenced by the variations or differences in stock indices. This article analyzes the differences between optimal portfolio performances based on these variations of stock indices. Based on a sample of 88 stocks from 10 stock indices over the last 10 years, divided into 3 data periods of stock price, we found no significant difference between optimal portfolio performances based on stock indices. We also found that no stock index can be the suitest for constructing a portfolio exhibiting optimal performance. Thus, the ability of a stock index to represent the performance of IHSG or whole stocks is the same as other stock indices. In this research, we also found that the line of risk-free returns to optimal portfolio performances, which were constructed without a short-selling approach, did not effectively engage the outermost boundary of the efficient portfolio frontier.